Human Resource Systems and Sustained Competitive Advantage: A Competency-Based Perspective - Lado, Augustine A.; Wilson, Mary (Academy of Management Review, 1994)
Augustine A. Lado, Mary C. Wilson, Human Resource Systems and Sustained Competitive Advantage: A Competency-Based Perspective, The Academy of Management Review, Vol. 19, No. 4 (Oct., 1994), pp. 699-727